2016
DOI: 10.18632/oncotarget.13559
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 2 is essential for maintaining cancer stem cell-like phenotype through activation of Hedgehog signaling pathway in colon cancer

Abstract: Cancer stem cells (CSCs) are a key target for reducing tumor growth, metastasis, and recurrence. Redox status is a critical factor in the maintenance of CSCs, and the antioxidant enzyme Peroxiredoxin 2 (Prdx2) plays an important role in the development of colon cancer. Therefore, we investigated the contribution of Prdx2 to the maintenance of stemness of colon CSCs. Here, we used short-hairpin RNAs and a Prdx2-overexpression vector to determine the effects of Prdx2. We demonstrated that knockdown of Prdx2 redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
(55 reference statements)
2
28
0
3
Order By: Relevance
“…The samples were frozen immediately and stored until use. Then, quantification of hub genes was performed by real-time PCR as described previously [ 48 ]. For survival analysis, we used the Kaplan-Meier method to analyze the correlation between overall survival and the hub genes, and the log-rank test was used to compare survival curves.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were frozen immediately and stored until use. Then, quantification of hub genes was performed by real-time PCR as described previously [ 48 ]. For survival analysis, we used the Kaplan-Meier method to analyze the correlation between overall survival and the hub genes, and the log-rank test was used to compare survival curves.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrosylation of PRDX2 can promote cardiac formation of mouse embryonic stem cells through X-box binding protein-1s/phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) signaling pathway (30); PRDX2 has also been shown to regulate the differentiation of embryonic stem cells into neurons (31). Compared with primary stem cells, the regulation of stem cell stemness by PRDX2 comes more from the study of cancer stem cells (6,32). Silencing PRDX2 gene resulted in the decrease of NANOG expression in colon cancer stem cells, and cell proliferation and migration were significantly reduced (6).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with primary stem cells, the regulation of stem cell stemness by PRDX2 comes more from the study of cancer stem cells (6,32). Silencing PRDX2 gene resulted in the decrease of NANOG expression in colon cancer stem cells, and cell proliferation and migration were significantly reduced (6). The expression of SRY-related high-mobility-group-box protein-2 and octamer-binding transcription factor-4 was down-regulated in PRDX2-silenced Huh7-H-Ras G12V hepatoma cells, and sphere formation efficiency and epithelial-mesenchymal transition were significantly inhibited (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a key member of PRDXs family, peroxiredoxin 2 (PRDX2) has been reported to scavenge peroxides and reactive oxygen species (ROS) in cells to regulate redox status, thus participating in a variety of cellular biological functions [14][15][16]. Recent studies identify aberrant expression of PRDX2 in several types of cancers and demonstrate that PRDX2 exerts an important role in cell proliferation, death, and drug sensitivity of cancer [17][18][19][20]. For example, it has been indicated that PRDX2 is upregulated in colorectal cancer and exerts a tumor promoting role in the progression of colorectal cancer [21,22].…”
Section: Introductionmentioning
confidence: 99%